6+2x+9=24+32+6x+12

Simple and best practice solution for 6+2x+9=24+32+6x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+2x+9=24+32+6x+12 equation:


Simplifying
6 + 2x + 9 = 24 + 32 + 6x + 12

Reorder the terms:
6 + 9 + 2x = 24 + 32 + 6x + 12

Combine like terms: 6 + 9 = 15
15 + 2x = 24 + 32 + 6x + 12

Reorder the terms:
15 + 2x = 24 + 32 + 12 + 6x

Combine like terms: 24 + 32 = 56
15 + 2x = 56 + 12 + 6x

Combine like terms: 56 + 12 = 68
15 + 2x = 68 + 6x

Solving
15 + 2x = 68 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
15 + 2x + -6x = 68 + 6x + -6x

Combine like terms: 2x + -6x = -4x
15 + -4x = 68 + 6x + -6x

Combine like terms: 6x + -6x = 0
15 + -4x = 68 + 0
15 + -4x = 68

Add '-15' to each side of the equation.
15 + -15 + -4x = 68 + -15

Combine like terms: 15 + -15 = 0
0 + -4x = 68 + -15
-4x = 68 + -15

Combine like terms: 68 + -15 = 53
-4x = 53

Divide each side by '-4'.
x = -13.25

Simplifying
x = -13.25

See similar equations:

| -7(10-10x)-8x= | | (3x+4)+(2x+2)=5(1x-1)+8 | | 2p-26=p | | 4(x-3)+18=3(x+3) | | 2x-3(x-5)=7 | | 6b-61=b+4 | | 6(3n-7)=84 | | 2x^4/5=25 | | x(x+2)=x(5+x) | | 10a+4(a+1)=32 | | 7(6+7a)= | | x^4+8x^3+14x^2-17x-42=0 | | -6+8(8a-8)= | | 3x-6+1x+30=7+8x+23-6x | | 42/168 | | 17x+4=x+35 | | 17v+58=3v+86 | | 2q=q+13 | | -10q-4q-6=18 | | 8v+4v= | | 10x-3(x-9)=9(x-1)+1 | | 2y-50=y-17 | | 6(9+11v)= | | -5n-6=7n+6 | | -3(4v-2)+v=4(v+3) | | a-b/9 | | 3u-62=4u-91 | | 6-1y=-2.3 | | 144=12(x-5) | | 80=23-3u | | 5[4x+6]=6x+9 | | -2r+1=-4r+9 |

Equations solver categories